(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines how the interplay of Karakalpak, Uzbek, and English influences English language acquisition among university students in Karakalpakstan. Moving beyond monolingual ELT frameworks, the study utilizes proficiency testing, surveys, and interviews to analyze how multilingual repertoires affect learning outcomes. Findings indicate that students possess enhanced metalinguistic awareness and strategic flexibility, despite structural interferences between Turkic and Germanic systems. The study argues for shifting the pedagogical lens to view multilingualism as a cognitive resource rather than a barrier. It concludes by proposing a plurilingual framework for higher education that integrates learners’ diverse linguistic ecologies into instructional practice.